2009
DOI: 10.1007/s10750-009-9885-7
|View full text |Cite
|
Sign up to set email alerts
|

Plant communities as a tool in temporary ponds conservation in SW Portugal

Abstract: Temporary ponds are seasonal wetlands annually subjected to extreme and unstable ecological conditions, neither truly aquatic nor truly terrestrial. This habitat and its flora have been poorly studied and documented because of the ephemeral character of the flora, the changeable annual weather that has a great effect on the small, herbaceous taxa and the declining abundance of temporary ponds. The objectives of this study are: (a) to define plant community diversity in terms of floristic composition of ephemer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 33 publications
(29 reference statements)
0
12
0
4
Order By: Relevance
“…A high floristic richness was reported in other Mediterranean areas with similar habitat types, e.g. Portugal (168 species in 29 ponds, Pinto‐Cruz et al , ), and Morocco (253 species in 48 ponds, Rhazi et al , ). Under conditions of increased water availability, where submerged and floating macrophytes were observed, Díaz‐Paniagua et al () reported a lower floristic richness with 55 plant species in 21 temporary ponds at Doñana National Park, Spain.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…A high floristic richness was reported in other Mediterranean areas with similar habitat types, e.g. Portugal (168 species in 29 ponds, Pinto‐Cruz et al , ), and Morocco (253 species in 48 ponds, Rhazi et al , ). Under conditions of increased water availability, where submerged and floating macrophytes were observed, Díaz‐Paniagua et al () reported a lower floristic richness with 55 plant species in 21 temporary ponds at Doñana National Park, Spain.…”
Section: Discussionmentioning
confidence: 70%
“…The habitat is characterized as follows: oligotrophic waters containing very few minerals, generally on sandy soils of the West Mediterranean, with Isoetes spp., which is characteristic of very shallow water (few centimetres) with a flooding period not longer than 2–3 months (European Commission, ). These hydrological conditions have been described for the shoreline of temporary ponds, with a typical concave basin morphology, which determines the small‐scale zonation of the vegetation, and for the entire pond surface of shallow temporary ponds with a flat morphology (Biondi and Bagella, ; Molina, ; Rudner, ; Paradis et al , ; Pinto‐Cruz et al , ; Bagella et al , ). The conservation value of Isoetion was pointed out nearly a century ago (Allorge, ; Braun‐Blanquet, ), and European legislation has recognized that it serves a key role in biodiversity conservation (Council of the European Communities, ; Bagella et al , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed conservation status of each pond using well-defined criteria selected from a comprehensive review of the literature (Grillas et al, 2004;Sala et al, 2004;Dimitriou et al, 2006;Fennessy et al, 2007;Stamati et al, 2008;Maes, 2013). This information was integrated and adapted using knowledge on the habitat and the region (Pinto-Cruz et al, 2009. Hence, the conservation status of each pond was assessed considering four parameters: (i) Topography-which is closely linked to the adequate hydroperiod, characterised by the timing and length of flooding, and water column depth; changes in hydroperiod have important effects in temporary waters, as they may change the pattern and strength of biotic interactions (Zacharias & Zamparas, 2010); (ii) Vegetation structure-a key parameter related to the habitat definition and presence of an ecological gradient, assessed by the number of vegetation belts.…”
Section: Pond Conservation Status Assessmentmentioning
confidence: 99%
“…Hence, the conservation status of each pond was assessed considering four parameters: (i) Topography-which is closely linked to the adequate hydroperiod, characterised by the timing and length of flooding, and water column depth; changes in hydroperiod have important effects in temporary waters, as they may change the pattern and strength of biotic interactions (Zacharias & Zamparas, 2010); (ii) Vegetation structure-a key parameter related to the habitat definition and presence of an ecological gradient, assessed by the number of vegetation belts. In this region, a well-preserved pond has three different vegetation belts (Pinto-Cruz et al, 2009); (iii) Impact of human activities-overall impact of the common anthropogenic activity on the condition of ponds (overgrazing, excavation, agriculture, hydrologic disturbance and tourism). The magnitude of a given disturbance is often more significant than the type of disturbance (Kantrud et al, 1989); and (iv) Trend of the pond area-the most important habitat feature for the conservation of a pond; if the pond area is stable or declining and in that case at which rate.…”
Section: Pond Conservation Status Assessmentmentioning
confidence: 99%